Student Political Transformations in Africa - Luescher, Thierry (International Higher Education, 2024)
<h3 id="as-higher-education-in-africa-is-undergoing-a-fast-expansion-student-politics-is-confronted-with-new-realities-and-undergoes-incisive-changes-they-can-be-observed-in-the-changing-political-character-of-student-governments-and-organizations-the-changing-role-of-student-representation-in-the-governance-of-african-universities-technological-changes-that-facilitate-a-changing-repertoire-of-students-political-agency-and-a-new-student-political-discourse-on-higher-education-in-africa-and-the-global-south" data-pm-slice="1 1 []">As higher education in Africa is undergoing a fast expansion, student politics is confronted with new realities and undergoes incisive changes. They can be observed in the changing political character of student governments and organizations, the changing role of student representation in the governance of African universities, technological changes that facilitate a changing repertoire of students’ political agency, and a new student political discourse on higher education in Africa and the Global South.